An Indirect Digital Technique to Transfer 3D Printed Casts to a Mechanical Articulator With Individual Sagittal Condylar Inclination Settings Using CBCT and Intraoral Scans. Issue 9 (6th August 2022) - Yang, Shengtao; Dong, Bo; Zhang, Qianqian; Li, Junying; Yuan, Quan; Yue, Li
Abstract: With the widespread application of digital impression techniques in prosthetic dentistry, accurate intraoral scan mounting, and virtual articulator parameters setting as per patients' anatomic structures are essential for treatment planning and restoration fabrication, especially for complex rehabilitation cases; meanwhile, marginal fit checking, occlusal adjustment, and porcelain layering of restorations are also crucial procedures in all cases in which the analog procedure to mount maxillary arches on a mechanical articulator is still required. This technique article presents an indirect digital approach that can first achieve virtual intraoral scan mounting and sagittal condylar inclination value setting of an Artex virtual articulator based on bony structures provided by a single cone beam computed tomography scan. It then facilitates the transfer of virtually mounted intraoral scans from the virtual articulator to the matched Artex mechanical articulator by relating a digitally scanned mounting plate of the Artex mechanical articulator to the virtual articulator, printing the intraoral scan and mounting plate scan assembly, and then mounting the printed casts on the mechanical articulator based on the printed mounting plate. This technique eliminates the conventional facebow transfer and protrusive bite registration procedures and offers a straightforward approach for the seamless integration of virtual environments and analog workflows into clinical practice. It aids in the design of restorations that are harmonious with the mandibular movements and reduces chairside adjustment time.